2011
DOI: 10.1111/j.1364-3703.2011.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Rice WRKY45 plays important roles in fungal and bacterial disease resistance

Abstract: Plant 'activators', such as benzothiadiazole (BTH), protect plants from various diseases by priming the plant salicylic acid (SA) signalling pathway. We have reported previously that a transcription factor identified in rice, WRKY45 (OsWRKY45), plays a pivotal role in BTH-induced disease resistance by mediating SA signalling. Here, we report further functional characterization of WRKY45. Different plant activators vary in their action points, either downstream (BTH and tiadinil) or upstream (probenazole) of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
186
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(200 citation statements)
references
References 60 publications
9
186
2
3
Order By: Relevance
“…OsWRKY45-1, derived from the subspecies Japonica, and OsWRKY45-2, derived from the subspecies indica, are a pair of allelic genes reported to have opposite effects on the resistance of rice plants to the bacteria pathogens Xoo and X. oryzae pathovar oryzicola (Xoc) (Tao et al 2011). However, a recent study with rice plants overexpressing OsWRKY45 derived from Nipponbare (NB) had strong resistance to Xoo (Tao et al 2011;Shimono et al 2012). Based on analysis of the pathogen response in OsWRKY22 knockout mutants and overexpression lines, OsWRKY22, coding for a Group III protein, played different roles in the defense response to fungi (Abbruscato et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…OsWRKY45-1, derived from the subspecies Japonica, and OsWRKY45-2, derived from the subspecies indica, are a pair of allelic genes reported to have opposite effects on the resistance of rice plants to the bacteria pathogens Xoo and X. oryzae pathovar oryzicola (Xoc) (Tao et al 2011). However, a recent study with rice plants overexpressing OsWRKY45 derived from Nipponbare (NB) had strong resistance to Xoo (Tao et al 2011;Shimono et al 2012). Based on analysis of the pathogen response in OsWRKY22 knockout mutants and overexpression lines, OsWRKY22, coding for a Group III protein, played different roles in the defense response to fungi (Abbruscato et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The WRKY45-ox rice plants showed strong preinvasive defense against rice blast (18). When Pb1-ox rice plants were inoculated with M. oryzae in leaf sheaths (25), fungal invasion into rice cells was observed from only 15-20% of fungal conidia, whereas the invasion rate was 80% in Nipponbare.…”
Section: Resultsmentioning
confidence: 99%
“…In rice, the SA pathway branches into OsNPR1-and WRKY45-dependent subpathways (15)(16)(17). WRKY45 is a transcriptional activator of group III and plays a major role in rice resistance to M. oryzae and Xoo induced by chemical inducers such as benzothiadiazole (BTH) (15,18). In Arabidopsis, NPR1 is regulated by the ubiquitin proteasome system (UPS) and a dual role has been proposed for this regulation: suppression of defense in the absence of pathogens and enhancement of the transcription triggered by SA signaling (19).…”
mentioning
confidence: 99%
“…Expression of a large number of WRKY genes is induced by pathogen (Lippok et al 2007). Furthermore, the rice salicylic acid (SA) pathway branches into WRKY45-regulated and NPR1 homologue (NH1)/Oryza sativa neuropeptide receptors-1 (OsNPR1)-regulated sub-pathways and WRKY45 conferred strong resistant to both rice blast and leaf blight diseases when overexpressed in rice (Shimono et al 2012). In the present study, the activation of the defense genes was studied to understand the level of expression following WBPH infestation at the reproductive stage.…”
Section: Vicheka Et Al: Defense Gene Expression To Wbph 457mentioning
confidence: 99%
“…OsWRKY45 plays a crucial role in the response to WBPH infestation in all rice plants. For instance, constitutive overexpression of OsWRKY45 in transgenic rice plants enhanced resistance to rice blast fungus (Shimono et al 2012). Goto et al (2015) reported that overexpression of OsWRKY45 could affect the tolerance of rice plants to low temperatures.…”
Section: Cereal Research Communications 45 2017mentioning
confidence: 99%